Analysis of Green Manufacturing Approach in SDGs-Based Tempeh Waste Management - Purnomo Purnomo; Nanta Sigit; Samgar (International Journal of Technology and Education Research, 2026)
Small and Medium Industries (SMEs) have an important role in the local economy, but often face challenges in environmentally friendly waste management. This study aims to examine tempeh waste in Tempe Sanan IKM and its management based on the principles of green manufacturing and SDGs, in order to formulate sustainable management recommendations for tempeh SMEs in Sanan Village, Malang, with reference to the principles of the Sustainable Development Goals (SDGs), especially the 6th goal (clean water and sanitation), the 12th (responsible consumption and production), and the 13th (handling climate change). The research method used is a qualitative case study with data collection techniques through in-depth interviews, direct observation, and documentation. The results of the analysis show that most of the Tempe Sanan SMEs have not fully implemented the principle of green manufacturing, especially in the aspect of liquid and solid waste treatment. However, there is great potential for the development of more sustainable waste treatment technology, such as the use of tempeh pulp waste into animal feed or organic fertilizer. This study recommends the need for support from local governments and related institutions in the form of training, incentives, and supporting infrastructure to encourage the transformation of SMEs towards greener and more sustainable industries.